When is Abuse a Crime? Canonical Criminal Perspective of Abuse - Sánchez-Girón Renedo, José Luis (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2024)
After the entry into force of the new Book VI of the CIC, the law of the Church includes new crimes of sexual abuse, either by admitting as perpetrators people who are not clerics (the only possible authors of these crimes previously), or by incorporating some new form of sexual abuse or new possible victims. This aside, some crimes referring to other types of abuse that were already in the CIC of 1983 remain; and there are spaces of possible abuse that have not been specifically classified as a crime. Apart from knowing which modalities are a crime and which are not at each moment in time, it is important to consider other elements of canon law, such as the prescription of criminal action.